2010
DOI: 10.1016/j.msec.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic adsorption of albumin on nanostructured TiO 2 thin films

Abstract: Spectroscopic ellipsometry was used to characterize the optical properties of thin (<5 nm) films of nanostructured titanium dioxide (TiO 2 ). These films were then used to investigate the dynamic adsorption of bovine serum albumin (BSA, a model protein), as a function of protein concentration, pH, and ionic strength. Experimental results were analyzed by an optical model and revealed that hydrophobic interactions were the main driving force behind the adsorption process, resulting in up to 3.5 mg/m 2 of albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 71 publications
7
23
0
Order By: Relevance
“…This finding indicates that the lateral interactions between the adsorbed BSA molecules are thus negligible at this pH. The obtained Langmuir fitting parameters (Table 2) show that the maximum attainable concentration of bound protein in a monolayer max amounts to an average value of 3.2 ± 0.3 mg/m 2 regardless of the nanospheres employed, in agreement with previously reported data for a close-packed monolayer of BSA [31,33,34,36]. The Langmuir's equilibrium constant Ä L , however, is found to increase as the diameter of the nanospheres decreases.…”
Section: Tablesupporting
confidence: 90%
See 1 more Smart Citation
“…This finding indicates that the lateral interactions between the adsorbed BSA molecules are thus negligible at this pH. The obtained Langmuir fitting parameters (Table 2) show that the maximum attainable concentration of bound protein in a monolayer max amounts to an average value of 3.2 ± 0.3 mg/m 2 regardless of the nanospheres employed, in agreement with previously reported data for a close-packed monolayer of BSA [31,33,34,36]. The Langmuir's equilibrium constant Ä L , however, is found to increase as the diameter of the nanospheres decreases.…”
Section: Tablesupporting
confidence: 90%
“…Other studies performed under similar pH conditions have reported, for example, average specific areas of ∼34 nm 2 per BSA molecule upon adsorption to titanium dioxide nanospheres of 25-30 nm in diameter [31]. The application of several optical surface-sensitive techniques for the investigation of BSA adsorption onto flat surfaces have also revealed that at the IEP of the protein an adsorbed monolayer of ∼4 nm thickness typically developed, clearly suggesting a side-on adsorption mode for BSA at equilibrium [33][34][35][36]. Interestingly, no difference in the specific area of adsorption was found at this pH as a function of the nanospheres size at saturation conditions.…”
Section: Tablementioning
confidence: 80%
“…To our knowledge, little work has been carried out to explore whether the food chain transmission and accumulation from Scenedesmus obliquus to D. magna can occur after a long period of exposure to nanoparticles. Nanomaterials can absorb heavy metals, surfactants, and other pollutants in water owing to their small size, large specific surface area, high surface energy, and strong adsorption ability (Wehmeyer et al 2010;Wang et al 2007). Thus, the effects of pollutants in water should be taken into account when the toxicity and accumulation of nanoparticles in organisms are being assessed (Kim et al 2013;Wang et al 2011).…”
mentioning
confidence: 99%
“…Since it measures the ratio of two values originated by the same signal, the measurements are highly accurate and reproducible. The measurements are complementary to the information obtained by QCM and can be used to determine the optical properties of asubstrate and the thickness of multiple layers on the surface.The technique is simple, nondestructive, has angstrom resolution, and has the capability of allowing the observation of the adsorption process inreal time[94, 134, 135]. The use of imaging ellipsometry can also provide spatial resolution of protein binding [136].…”
Section: Techniques To Investigate Protein Adsorptionmentioning
confidence: 99%